Applications of Food Irradiation Technology - Singh, Rita; Singh, Antaryami (Defence Life Science Journal, 2020)
Food irradiation provides an effective means for controlling the physiological processes causing spoilage and for eradication of microbes, insect pests and parasites. Irradiation has multipurpose role in food processing and is applicable for a variety of food commodities such as fruits, vegetables, cereals, pulses, spices, meat, poultry and seafood. Several years of scientific research, evaluation, and testing have resulted in regulatory approvals for the food irradiation technology in a number of countries. Commercial application of this technology has greatly advanced in recent years following the approval of the health authorities of different countries. This review summarises the applications of irradiation technology in controlling pathogens and food spoilage, and the development of irradiation treatment worldwide.